2014
DOI: 10.1074/jbc.m114.598938
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Function Is Regulated by B56α-mediated Targeting of Protein Phosphatase 2A (PP2A) to Contractile Relevant Substrates

Abstract: Background: PP2A is a regulator of cardiac excitation-contraction coupling. Results: Cardiomyocyte-directed overexpression of B56␣, the main cardiac PP2A regulatory subunit, results in the dephosphorylation of myofilament proteins, increased Ca 2ϩ sensitivity, and higher contractility. Conclusion: This suggests an important role for B56␣ in regulating PP2A activity and thereby the contractile function. Significance: PP2A-B56␣ is a potential pharmacological target to improve cardiac performance in failing heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 52 publications
4
44
1
Order By: Relevance
“…Contrary to our results, the deficiency of B56α (another regulatory of PP2A), which is an autoinhibitor of cardiac PP2A activity, resulted in increased PP2A activity [13]. However, some studies revealed that B56α deficiency may decrease PP2A activity too, and overexpression of B56α enhanced PP2A activity in the heart [13,20]. It is possible that different regulatory subunits of PP2A have different influences in PP2A activity.…”
Section: Discussioncontrasting
confidence: 97%
“…Contrary to our results, the deficiency of B56α (another regulatory of PP2A), which is an autoinhibitor of cardiac PP2A activity, resulted in increased PP2A activity [13]. However, some studies revealed that B56α deficiency may decrease PP2A activity too, and overexpression of B56α enhanced PP2A activity in the heart [13,20]. It is possible that different regulatory subunits of PP2A have different influences in PP2A activity.…”
Section: Discussioncontrasting
confidence: 97%
“…Physiologically, these phenotypes resulted in reduced heart rate, heart rate variability, conduction abnormalities and resistance to catecholamine-induced arrhythmias, highlighting the potential of targeting specific PP2A subunits therapeutically [21]. Interestingly, a second study has shown that acute overexpression of B56α may lead to increased PP2A activity in the cytoplasm and myofilament fractions of heart lysates [76]. This may indicate differential functions of B56α depending on cellular compartment that may be facilitated by the phosphorylation of B56α at Ser41 (modifies PP2A-C-B56α affinity) [43,76].…”
Section: Pp2a Regulation In Diseasementioning
confidence: 99%
“…Interestingly, a second study has shown that acute overexpression of B56α may lead to increased PP2A activity in the cytoplasm and myofilament fractions of heart lysates [76]. This may indicate differential functions of B56α depending on cellular compartment that may be facilitated by the phosphorylation of B56α at Ser41 (modifies PP2A-C-B56α affinity) [43,76]. B56α has also been implicated in the pathophysiology of “Ankyrin-B Syndrome”, as the loss of ankyrin-B function, essential to B56α localization, may lead to altered RyR2 phosphorylation and arrhythmia [43,77].…”
Section: Pp2a Regulation In Diseasementioning
confidence: 99%
“…This indicates that fibrosis selectively increases the phosphorylation level of troponin I. Szymanska et al reported that the responses to adrenergic stimulation differed between PLN and troponin I [28]. Kirchhefer et al reported that protein phosphatase 2A activity differed among RyR, PLN, and troponin I [29]. Kuo et al showed that reduced expression of polycystin 2, which senses fluid stress, increased the phosphorylation level of cardiac troponin I with a reduced phosphorylation level of PLN [30].…”
Section: Discussionmentioning
confidence: 99%